Detection of Cu2+ in Water Based on Histidine-Gold Labeled Multiwalled Carbon Nanotube Electrochemical Sensor - Rilong Zhu; Gangqiang Zhou; Fengxia Tang; Chunyi Tong; Yeyao Wang; Jinsheng Wang (International Journal of Analytical Chemistry)
Based on the strong interaction between histidine and copper ions and the signal enhancement effect of gold-labeling carbon nanotubes, an electrochemical sensor is established and used to measure copper ions in river water. In this study the results show that the concentrations of copper ion have well linear relationship with the peak current in the range of 10−11–10−7 mol/L, and the limit of detection is 10−12 mol/L. When using this method to detect copper ions in the Xiangjiang River, the test results are consistent with the atomic absorption method. This study shows that the sensor is convenient to be used in daily monitoring of copper ions in river water.